Zinc deficiency as a contributor to acute kidney injury in patients with chronic kidney disease: a propensity score–matched retrospective analysis - Lai, Yi-Chen; Yu, Ting-Sian; Hung, Kuo-Chuan; Wu, Jheng-Yan; Tan, Ping-Heng; Ho, Chun-Ning; Hung, I-Yin; Lin, Chien-Ming; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundAcute kidney injury (AKI) is a frequent and serious complication in patients with chronic kidney disease (CKD) that often leads to poor clinical outcomes. Despite the biological plausibility of linking zinc deficiency (ZD) to increased AKI susceptibility, large-scale evidence evaluating this association in the CKD population remains scarce.MethodsThis retrospective cohort study utilized the TriNetX Analytics Network Platform to identify patients aged ≥18 years with pre-existing CKD who underwent serum zinc testing between January 2010 and December 2023. Patients were categorized into zinc deficiency (ZD: <70 μg/dl) and control groups (70–120 μg/dl). After applying the exclusion criteria and 1:1 propensity score matching for demographics, comorbidities, laboratory parameters, and medications, we analyzed 5,619 patients per group. The primary outcome was new-onset AKI at the 12-month follow-up, with secondary outcomes including risk of mortality, end-stage renal disease (ESRD), intensive care unit (ICU) admission, and major cardiac adverse events (MCAEs).ResultsAt 12 months, zinc-deficient patients experienced significantly higher risks of AKI [19.3 vs. 14.9%; hazard ratio (HR): 1.37, 95% confidence interval (CI): 1.25–1.50, P < 0.001], mortality (9.0 vs. 4.8%; HR 1.95, 95% CI 1.68–2.26, P < 0.001), ESRD progression (1.9 vs. 1.4%; HR 1.40, 95% CI 1.04–1.88, P = 0.025), and ICU admissions (8.7 vs. 5.8%; HR 1.56, 95% CI 1.35–1.79, P < 0.001). The effects were stronger at 6 months than at 12 months, suggesting rapid manifestation. Notably, these zinc-specific effects persisted even after excluding patients who developed malnutrition, reinforcing that the observed associations were attributable to zinc deficiency rather than general nutritional status. Subgroup analyses demonstrated consistent findings across diverse patient characteristics.ConclusionsBaseline zinc deficiency is an independent, modifiable risk factor for AKI development and mortality in patients with CKD. These findings support routine zinc status assessments and targeted supplementation strategies in CKD management protocols. However, the observational design and single-point zinc measurements limit the causal inferences. Prospective randomized controlled trials are needed to determine whether zinc supplementation can prevent AKI and improve outcomes in patients with CKD.